Relative biological effectiveness (RBE) and distal edge effects of proton radiation on early damage in vivo. (2nd November 2017) - Sørensen, Brita Singers; Bassler, Niels; Nielsen, Steffen; Horsman, Michael R.; Grzanka, Leszek; Spejlborg, Harald; Swakoń, Jan; Olko, Paweł; Overgaard, Jens
Abstract: Introduction: The aim of the present study was to examine the RBE for early damage in an in vivo mouse model, and the effect of the increased linear energy transfer (LET) towards the distal edge of the spread-out Bragg peak (SOBP). Method: The lower part of the right hind limb of CDF1 mice was irradiated with single fractions of either 6 MV photons, 240 kV photons or scanning beam protons and graded doses were applied. For the proton irradiation, the leg was either placed in the middle of a 30-mm SOBP, or to assess the effect in different positions, irradiated in 4 mm intervals from the middle of the SOBP to behind the distal dose fall-off. Irradiations were performed with the same dose plan at all positions, corresponding to a dose of 31.25 Gy in the middle of the SOBP. Endpoint of the study was early skin damage of the foot, assessed by a mouse foot skin scoring system. Results: The MDD50 values with 95% confidence intervals were 36.1 (34.2–38.1) Gy for protons in the middle of the SOBP for score 3.5. For 6 MV photons, it was 35.9 (34.5–37.5) Gy and 32.6 (30.7–34.7) Gy for 240 kV photons for score 3.5. The corresponding RBE was 1.00 (0.94–1.05), relative to 6 MV photons and 0.9 (0.85–0.97) relative to 240 kV photons. In the mice group positioned at the SOBP distal dose fall-off, 25% of the mice developed early skin damage compared with 0–8% in other groups. LETd, z = 1 was 8.4 keV/μm at the distal dose fall-off and the physical dose delivered was 7% lower than in the central SOBP position, where LETd, z =1 was 3.3 keV/μm. Conclusions: Although there is a need to expand the current study to be able to calculate an exact enhancement ratio, an enhanced biological effect in vivo for early skin damage in the distal edge was demonstrated.